2023
DOI: 10.1111/risa.14204
|View full text |Cite
|
Sign up to set email alerts
|

How people decide who is correct when groups of scientists disagree

Abstract: Uncertainty that arises from disputes among scientists seems to foster public skepticism or noncompliance. Communication of potential cues to the relative performance of contending scientists might affect judgments of which position is likely more valid. We used actual scientific disputes—the nature of dark matter, sea level rise under climate change, and benefits and risks of marijuana—to assess Americans’ responses (n = 3150). Seven cues—replication, information quality, the majority position, degree source,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 159 publications
(251 reference statements)
0
2
0
Order By: Relevance
“…They discussed the importance of trusting the source research or agency, the reputation of the scientist, and the agency (government or independent), as well as having lower trust in media and friends, and that a scientist's ability to communicate also influences the Lay Public's perceived trustworthiness of that scientist. Research has demonstrated that we rely on trust in, experience of, and knowledge about, a communicator to judge communications when we do not fully understand the message (Renn and Levine, 1991;Hocevar et al, 2017;Johnson et al, 2023). Research has also shown that individuals use various indicators of trust as a heuristic to evaluate scientific information, such as recognizing an organization's logo or stamp on a message or image (Bica et al, 2019).…”
Section: Other Lessons For Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…They discussed the importance of trusting the source research or agency, the reputation of the scientist, and the agency (government or independent), as well as having lower trust in media and friends, and that a scientist's ability to communicate also influences the Lay Public's perceived trustworthiness of that scientist. Research has demonstrated that we rely on trust in, experience of, and knowledge about, a communicator to judge communications when we do not fully understand the message (Renn and Levine, 1991;Hocevar et al, 2017;Johnson et al, 2023). Research has also shown that individuals use various indicators of trust as a heuristic to evaluate scientific information, such as recognizing an organization's logo or stamp on a message or image (Bica et al, 2019).…”
Section: Other Lessons For Communicationmentioning
confidence: 99%
“…Given most of our Lay Public appear to base their understanding on their personal experiences and public releases of information, announcements, summaries in the media and social media, the NHE information they construct their mental models from is inherently 10.3389/fcomm.2024.1366995 Frontiers in Communication 14 frontiersin.org simplified along scientific dimensions, compared to the information used by and familiar to active or previously-active/trained scientists. Thus, to make meaning from this information and help reconcile any gaps in information or understanding, they thus draw on these other 'observable' features such as who the scientist is, and their prior experience of that communicator (Johnson et al, 2023). The Lay Public's use of these other factors to understand (and respond to) information has also been recognized in various risk communication models (see section 1), including the Risk Information Seeking and Processing Model that recognizes people draw on a range of social, psychological, and communicative factors in seeking and interpreting information (Yang et al, 2014), the Community Engagement Theory model that highlights the importance of trust for effective risk communication (Paton, 2019), and the IDEA model's internalization and explanation factors (whether people see the risk as relevant to them, understand it, and think it is trustworthy and credible; Sellnow et al, 2017).…”
Section: Other Lessons For Communicationmentioning
confidence: 99%